SOCIALIZATION OF GROUP ACTIVITY THERAPY ON THE LEVEL OF DEPRESSION IN THE ELDERLY IN GAMPONG KEURAMAT, KUTA ALAM DISTRICT, BANDA ACEH CITY - Jannah, Miftahul; Yanti, Ira Dama; Yeni, Manovri; Laila, Nurnarita (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2022)
Based on data from the World Health Organization (2017), the prevalence of depression in the elderly in the world ranges from 10-15% of the elderly population, while the prevalence of depression in Indonesia is 11.6% of the elderly. In Gampong Keuramat, Kuta Alam District, Banda Aceh City, the elderly population is 1,041 people, but there are still many who do not know about the benefits of Group Activity Therapy (GAT) to reduce depression levels in the elderly. GAT is a series of activities that help facilitate the socialization skills of several elderly people with social relationship problems. This therapy is widely used to reduce anxiety or depression in the elderly. On this basis, the D3 Physiotherapy Study Program of the Vocational Faculty of the University of Muhammadiyah Aceh held a GAT activity in Gampong Keuramat, Kuta Alam District, Banda Aceh City. This activity is one of Community Service which is part of the Tri Dharma of Higher Education. The purpose of holding this activity is as follows: 1) To help the elderly in socializing and reduce the level of depression in the elderly; 2) To increase the sense of community in the elderly; 3) To improve physical and spiritual health in the elderly. It is hoped that this activity will not only be carried out in Keuramat Village, but will be carried out in all villages in Banda Aceh City, so that the creation of a healthy elderly, prosperous elderly, and happy society.Keywords: GAT, Depression, Healthy Elderly, Gampong Keuramat Banda Aceh City.